2021
DOI: 10.1371/journal.pone.0252758
|View full text |Cite
|
Sign up to set email alerts
|

Sex and kidney ACE2 expression in primary focal segmental glomerulosclerosis: A NEPTUNE study

Abstract: Background Angiotensin-converting enzyme 2 (ACE2) has been implicated in the pathogenesis of experimental kidney disease. ACE2 is on the X chromosome, and in mice, deletion of ACE2 leads to the development of focal segmental glomerulosclerosis (FSGS). The relationship between sex and renal ACE2 expression in humans with kidney disease is a gap in current knowledge. Methods We studied renal tubulointerstitial microarray data and clinical variables from subjects with FSGS enrolled in the Nephrotic Syndrome Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…Recent studies have shown that angiotensin-converting enzyme 2 (ACE2) expression is also associated with interstitial brosis and tubular atrophy in men and correlates with TGF-β1 in patients with FSGS studied by the Nephrotic Syndrome Research Network using renal tubular interstitial microarray data and clinical variables (Maksimowski et al 2021). The results of this study were consistent with those of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have shown that angiotensin-converting enzyme 2 (ACE2) expression is also associated with interstitial brosis and tubular atrophy in men and correlates with TGF-β1 in patients with FSGS studied by the Nephrotic Syndrome Research Network using renal tubular interstitial microarray data and clinical variables (Maksimowski et al 2021). The results of this study were consistent with those of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Although developed as a model of Alport Syndrome, studies of Col4a3 -/mice may also provide insights into the pathogenesis of a wider spectrum of kidney disease because the Col4a3 gene plays a role in both sporadic and familial FSGS as well as diabetic nephropathy [19,20]. Moreover, changes in the TI of the kidney, in particular fibrosis and tubular atrophy, correlate inversely with GFR [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Male gender is already identified as a factor associated with the occurrence of an AKI during Covid [18] [19]. One hypothesis was the overexpression of ACE2 in male subjects [20]. Androgenic hormones would also play a role in increasing the expression of ACE2 [21].…”
Section: Discussionmentioning
confidence: 99%